Antimicrobial activity of immobilized lactoferrin and lactoferricin. Issue 8 (19th October 2016) - Chen, Renxun; Cole, Nerida; Dutta, Debarun; Kumar, Naresh; Willcox, Mark D. P.
Abstract: Lactoferrin and lactoferricin were immobilized on glass surfaces via two linkers, 4‐azidobenzoic acid (ABA) or 4‐fluoro‐3‐nitrophenyl azide (FNA). The resulting surfaces were characterized by X‐ray photoelectron spectroscopy (XPS) and contact angle measurements. The antimicrobial activity of the surfaces was determined using Pseudomonas aeruginosa and Staphylococcus aureus strains by fluorescence microscopy. Lactoferrin and lactoferricin immobilization was confirmed by XPS showing significant increases ( p < 0.05) in nitrogen on the glass surface. The immobilization of both proteins slightly increased the overall hydrophobicity of the glass. Both lactoferrin and lactoferricin immobilized on glass significantly ( p < 0.05) reduced the numbers of viable bacterial cells adherent to the glass. For P. aeruginosa, the immobilized proteins consistently increased the percentage of dead cells compared to the total cells adherent to the glass surfaces ( p < 0.03). Lactoferrin and lactoferricin were successfully immobilized on glass surfaces and showed promising antimicrobial activity against pathogenic bacteria. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 105B: 2612–2617, 2017.